Designing high-performance amplifiers - Feucht, Dennis (Feucht, Dennis. Analog circuit design series ;, 2010)
"The Analog Circuit Design set reduces the concepts of analog electronics to their simplest, most obvious form which can easily be applied (even quantitatively) with minimal effort. The emphasis of the set is to help you intuitively learn through inspection how circuits work and apply the same techniques to circuits of the same class. The third volume High Performance Amplifiers applies the concepts from the first two volumes (see related titles below). It is an advanced treatment of amplifier design/analysis emphasizing both wideband and precision amplification. Topics include bandwidth extension, noise and distortion, effects of components, instrumentation and isolation amplifiers, autocalibration, thermal effects, current-feedback amplifiers, multi-path schemes, feed forward, fT multipliers, buffers, voltage translators, Giulbert gain cells and multipliers."--Publisher's website.